Gas Seepage along the Edge of the Aquitaine Shelf (France): Origin and Local Fluxes. (24th July 2017) - Ruffine, Livio; Donval, Jean-Pierre; Croguennec, Claire; Bignon, Laurent; Birot, Dominique; Battani, Anne; Bayon, Germain; Caprais, Jean-Claude; Lantéri, Nadine; Levaché, Denis; Dupré, Stéphanie
Abstract : During the scientific expedition GAZCOGNE2 at the Bay of Biscay nine gas seeps were sampled for the first time and their flux was measured using an in situ pressure-preservation sampler (PEGAZ, © IFREMER). Overall, three sites were investigated to determine the nature and the origin of the gases bubbling at the seafloor and forming acoustic plumes into the water column, as this was the question raised from the first geologic study of the area. This has guided our study and accordingly corresponds to the main purpose of the present article. Thus, the molecular and isotopic ( δ D and δ 13 C) analyses revealed that the gas seeps were primarily composed of methane. Both methane and ethane are of microbial origin, and the former has been generated by microbial reduction of carbon dioxide. Heavier hydrocarbons accounted for less than 0.06% mol of the total amount. Despite the microbial origin of methane, the samples exhibit subtle differences with respect to the δ 13 C C H 4 values, which varied between −72.7 and −66.1‰ . It has been suggested that such a discrepancy was predominantly governed by the occurrence of anaerobic methane oxidation. The PEGAZ sampler also enabled us to estimate the local gas fluxes from the sampled streams. The resulting values are extremely heterogeneous between seeps, ranging from 35 to 368 mLn·min −1 . Assuming a steady discharge, the mean calculated methane emission for the nine seeps is of 38 kmol·yr −1 . Considering the extent of the seep area, this very local estimate suggests that the Aquitaine Shelf is a very appropriate place to study methane discharge and its fate on continental shelves.